ANTIDIABETIC EFFECT OF ETHANOLIC EXTRACT OF KEDONGDONG PAGAR LEAVES (Lannea coromandelica (Houtt.) Merr.) ON MALE MICE - Safriana Safriana; Melati Yulia Kusumastuti; Andilala Andilala (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Diabetes mellitus is a metabolic condition defined as an increase in blood glucose levels (hyperglycemia) caused by impaired insulin production or insulin action. One of the treatments for diabetes mellitus is the use of medicinal plants because they contain bioactive phytochemicals. Kedongdong pagar leaves (Lannea coromandelica (Houtt.) Merr.) is an empirical medication used to reduce the blood glucose levels in Aceh, Indonesia. The leaves contain flavonoids, which have antioxidant effects that can reduce damage to the pancreatic beta cells. The goal of this study was to examine the antidiabetic impact of an ethanol extract of kedongdong pagar leaves in male mice induced with alloxan to increase blood glucose levels. The test procedure involved splitting 25 mice into five treatment groups, Na-CMC suspension 0.5% w/v, Kedongdong pagar extract with dose 10 mg/kg BW, 20 mg/kg BW, 40 mg/kg BW, and glibenclamide suspension with dose 0.65 mg/kg BW as positive control. The results showed that all ethanolic extracts of Lannea coromandelica had the same potency to lower blood glucose levels in mice, implying that the ethanol extract of Lannea coromandelica leaves had antidiabetic activity due to the presence of antidiabetic compounds such as flavonoids and glycosides. Keywords: Antidiabetic, Diabetic, Kedongdong Pagar Leaves, Lannea coromandelica.